Шляхи підвищення конкурентоспроможності залізниці - Куделя, В. І. (НТУ "ХПІ", 2015)
В статті виділені недоліки, що існують в розвитку транспортної галузі. Розглянуті основні напрямки конкуренції в яких діє залізниця на ринку транспортних послуг. Підкреслено, що в умовах ринкових відносин залізничний транспорт повинен швидко реагувати на зміну попиту на перевезення і підвищувати конкурентоспроможність шляхом покращення якості вантажних перевезень і підвищення ефективності обслуговування виробництва і населення. А також виділені шляхи підвищення конкурентоспроможності залізниці.

The article highlights the shortcomings that exist in the development of the transport industry. The main areas of competition in which the railroad operates in the market of transport services. It is noted that in conditions of market relations the rail transport needs to respond quickly to changing traffic demand and increase competitiveness by improving the quality of freight transport and improving the efficiency of service production and population. Considered the main indicators of the quality of transport services that characterize freight and passenger transportation. It is noted that the development of a competitive transport market requires the creation of conditions for exceeding the level of supply of high-quality transport services over the demand, as well as publicity and information of market opening on prices and quality of services. This will give consumers a free choice of transport services, make price and quality competition. The mechanism of "price-quality" will stimulate studies of demand for various categories of services and to evaluate the level of competitors, to improve the quality of transport services, to find the optimal balance between price and quality. The article also highlighted ways to improve the competitiveness of the railway. It is concluded that in modern conditions, in order to achieve success, the railroad must develop a flexible system of quality management of transport services, to properly assess these activities and their impact on the final result of the activity depending on the competitive situation on the transport market.
Ways of increasing the competitiveness of Railways
Keywords: залізничний транспорт; конкуренція; якість перевезень; транспортний ринок; гнучкі тарифи; competition; competitiveness; quality of transport; transport market; railway road